6 The relationship between agriculture background and student's perception of self in an animal science department. (7th December 2018) - Early, N; Chang, C; Wickersham, T
Abstract: More students are entering departments of animal science without prior agriculture experience, placing responsibility more profoundly on the departments to provide the industry context and disciplinary knowledge necessary for graduate success in animal science careers. Therefore, contemporary teaching in animal science programs requires approaches to address these needs. Our objective was to investigate the relationships between a student's agriculture background and their perception of self in an animal science department at Texas A&M University. During class, students (n = 146) in animal nutrition, a core animal science course, completed the Self-Perception Profile for College Students, previously developed at the University of Denver. The instrument measures self-perceived competence in and importance of 14 domains determined to be meaningful to college-aged students. A domain's discrepancy score was calculated as competence minus importance, such that a negative score indicates a need for improved competence in that domain. Multiple regression was used to determine the relationship between a respondent's agriculture background and their discrepancy score in each domain, controlling for the following associated covariates: GPA, age, gender, study area emphasis, classification and transfer status. Discrepancy score means for students from agriculture backgrounds were significantly ( P < 0.05) greater in the scholastic (0.40), close friendship (0.07), and animal science knowledge (0.08) domains compared to the discrepancy score means of students without agriculture backgrounds (0.05, -0.14 and -0.77 respectively). Non-agriculture background student's negative discrepancy scores in the close friendships and animal science knowledge domains indicate a need for improved competence in these areas. Qualitative data collected concurrently supported these findings. Teaching strategies such as collaborative work, peer instruction and experiences that expose non-agriculture students to animal science knowledge in novel ways should be tested as a means of improving students' self-perceived competence in these domains.